Use of the AHP matrix for selecting Lean tools in the healthcare area - Guimarães, Camille Pereira; Araujo, Andressa Clara Barbosa de; Santos, Barbara Emanuelle Cavalcante dos; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2025)
Lean Healthcare is a methodology based on the principles of Lean Manufacturing applied in health units. This philosophy is of great importance for health in Brazil, since it reduces overcrowding, waiting time, costs and ensures continuous improvement in patient health care. This work aims to select the Lean tools that most impact waste in the health area. The Hierarchical Analysis Method (AHP) was applied, which aims to compare and evaluate the options based on multicriteria following the respective steps: definition of criteria; hierarchy of criteria; comparison of options; calculation of priority and selection of the best option; and analyzing the results obtained from the calculation of the priorities of each tool. Thus, the criteria are 8 tools and the 8 wastes of lean production. In the result of the hierarchical comparison, Value Stream Mapping (VSM) stands out as the tool with the greatest impact for the study and mitigation of waste in Lean Healthcare. It is noted that the MFV's ability to visualize processes encourages the identification of unnecessary activities and sources of waste in health units, improving the management and functioning of hospitals and, consequently, promoting safety and quality in patient care.
Keywords: hierarchical analysis; decision making; lean; Health